Writing the Worlds of Our Fathers and Mothers: The Fall and Rise of American Jewish Labor History - Breitzer, Susan Roth (History compass, 2011)
American Jewish labor history stands out as a place where labor, immigration, Jewish, and other specialties meet and interact - often uneasily. The changing fortunes of this area of study have not always coincided with those of American Jewish history, which was established as a field well in advance of the rise of the new social history. As a result, American Jewish labor history became marginalized just as American Jewish history as a field had become mainstream enough to become comfortably critical as opposed to self-consciously celebratory. Part of the reason for this has been a relatively narrow geographic and chronological focus, as well as an emphasis on institutions and lack of attention to (or even dismissiveness) of gender issues. Additionally, the focus has traditionally been more celebratory and memoiristic than critical, due to the fact that most of the earliest published histories have been written by former activists. In addition, the general narrative, popularized by Irving Howe’s The World of our Fathers has made the Lower East Side tailor the symbol and stereotype of the Jewish worker. In the last decade, however, more critical approaches, as well crossover scholarship from the fields of women’s, immigration, and labor history, have resulted in the study themes and topics that have been previously ignored or slighted, as well as new approaches that incorporate gender, social history, and comparative perspectives and challenge long-accepted conventional wisdom.